UJI AKTIVITAS SALEP EKSTRAK ETANOL DAUN JAMBU BIJI (Psidium guajava Linn.) TERHADAP LUKA BAKAR DERAJAT II PADA TIKUS JANTAN PUTIH - Triyani Sumiati; Devi Ratnasari; Liana Febriyani (Sekolah Tinggi Teknologi Industri dan Farmasi Bogor, 2017)
Psidium guajava Linn. known as guava leaves is a medicinal plant that has been used to treat diseases, including burns medicine. From the results of the study note that the extract of guava leaves ethanol can heal burns. To facilitate its use, then made ointment preparations of guava ethanol extracts. The purpose of this research is to make an ointment formula ethanol extract of guava leaves which has a healing effectiveness on a second degree burns. Extraction of guava leaf made by the process of maceration, then the liquid extract was concentrated by rotary evaporator to obtain a concentrated extract of guava leaf. An ointment formulations ethanol extract of guava leaf are made with concentrations respectively 30%, 35%, and 40. The effectiveness test of the healing of burns grade II using 5 groups: negative control (ointment base), positive control (Bioplacenton®), ointments ethanol extract of guava leaves 30%, 35%, and 40%. The study was conducted . of male white rats with severe between 200 – 400 grams. Observations up to 21st day. These result by using Tukey Test indicate that the concentration of guava leaf extract 35% , The results of this study indicate that the variation concentration of guava leaf extract gives a healing effect that does not differ significantly to healing second degree burns in male white rats.